KEPERCAYAAN MEREK DAN BRAND AFFECT SEBAGAI ANTESEDEN DARI LOYALITAS MEREK - Sri Rahayu; Mugi Harsono (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2018)
The purpose of this paper is to explain the important role of brand and brand loyalty inmarketing activities. This paper also explains the antecedents of brand loyalty. The role of a branddoes not only actas a name, but also increasing the company's competitive advantage. The benefitsof a brand for consumers are, among many others, for emotional, self and social expression,attitudes, values and culture benefits. In the mean time, the role of brand loyalty in marketingis to contribute to the survival of the company, to increase new customer opportunities as well asto reduce marketing costs. To improve a brand loyalty, a companyshould increase its brand trustin advance as it plays an important role in improving brand loyalty. A cpmpany brand trust hastwo dimensions of intention and reliability. Brand affect, on the other hand, is an important forimproving a brand loyalty. Therefore,a company’sbrand trust and brand affect should be improvedfor the brand loyalty to improve as well.Key words : Brand trust, Brand Affect, Brand Loyalty